MAKSIMALISASI KEUNTUNGAN PADA PRODUK OLAHAN UBI KAYU DENGAN MENGGUNAKAN LINIER PROGRAMMING METODE SIMPLEK - Eri Yusnita Arvianti; Kusnia Rindi A.S (BUANA SAINS, 2011)
Company cassava chips "dolphin" is one of the agro-industry that can compete with other agro-and agro-industries can increase sales of their products so they can get maximum benefit. So that could be done using linear programming is by using the simplex method. Based on the results obtained by the company gets the maximum profit of IDR 4.04 million/day within 1 week maximum profit of IDR 24.24 million in a month so the maximum profit of IDR 105,040,000,- and known to the optimal production of cassava chips cassava chips located on the sweet taste with the production of 950 kg/day. While for cassava chips savory flavors produce only 350 kg/day